MODY in Siberia – molecular genetics and clinical characteristics - Alla Konstantinovna Ovsyannikova; Oksana Dmitrievna Rymar; Elena Vladimirovna Shakhtshneider; Elena Nikolaevna Voropaeva; Dinara Evgenevna Ivanoshchuk; Mikhail Ivinovich Voevoda (Сахарный диабет)
The diagnosis of maturity onset diabetes of the young (MODY) has high clinical significance in young patients (no absolute need for exogenous insulin; normoglycaemia in most patients achieved by dieting or taking oral hypoglycaemic agents) and their relatives (high probability of first-degree relatives being carriers of mutations, which requires a thorough collection of family history and determination of the parameters of carbohydrate metabolism). Aim. This study aimed was to determine the clinical characteristics of different subtypes of MODY in a Siberian region. Materials and Methods. We performed an examination, biochemical and hormonal blood tests, ultrasound and molecular genetic testing of 20 patients with a clinical diagnosis of MODY. Results. Four subtypes of MODY were verified: MODY2 in 11 patients, MODY3 in two, MODY8 in one and MODY12 in two. Eleven patients (69%) exhibited no clinical manifestations of carbohydrate metabolism disorders, and one patient showed weight loss during early stage of the disease. Comorbidities included dyslipidemia, thyroid gland disorders and arterial hypertension. One patient (6%) exhibited diabetic nephropathy; two (13%), diabetic retinopathy and three (19%), peripheral neuropathy of lower legs. All patients achieved the target carbohydrate metabolism; the level of C-peptide was within the reference range. Conclusion. Four different subtypes of MODY (2, 3, 8, 12) were diagnosed in the present study, which differed in their clinical characteristics, presence of complications and treatment strategies. Our knowledge of monogenic forms of diabetes is expanding with the development in molecular genetics, but several aspects related to them require further study.